2001
DOI: 10.1128/jb.183.17.5198-5202.2001
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and Mechanism of Action of the Small Heat Shock Protein from the Hyperthermophilic Archaeon Pyrococcus furiosus

Abstract: The small heat shock protein (sHSP) from the hyperthermophile Pyrococcus furiosus was specifically induced at the level of transcription by heat shock at 105°C. The gene encoding this protein was cloned and overexpressed in Escherichia coli. The recombinant sHSP prevented the majority of E. coli proteins from aggregating in vitro for up to 40 min at 105°C. The sHSP also prevented bovine glutamate dehydrogenase from aggregating at 56°C. Survivability of E. coli overexpressing the sHSP was enhanced approximately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 39 publications
4
29
0
Order By: Relevance
“…Our results indicated that Pfds and sHsps have analogous roles as they both improve the efficiency of Hsp60 catalysis. Hsp60 and Pfd subunits in P. furiosus are constitutively expressed (data not shown) whereas the sHsp is highly induced by heat shock treatment at 1058C (Laksanalamai et al, 2001). In addition, after P. furiosus cells are removed from heat shock conditions and restored to growth conditions (958C), the levels of mRNA and protein appear to decrease rapidly as detected by Northern and Western blot, respectively (Laksanalamai, Lowe and Robb, unpublished results).…”
Section: Stabilization Of Taq Polymerase By a Combination Of Prefoldimentioning
confidence: 92%
See 4 more Smart Citations
“…Our results indicated that Pfds and sHsps have analogous roles as they both improve the efficiency of Hsp60 catalysis. Hsp60 and Pfd subunits in P. furiosus are constitutively expressed (data not shown) whereas the sHsp is highly induced by heat shock treatment at 1058C (Laksanalamai et al, 2001). In addition, after P. furiosus cells are removed from heat shock conditions and restored to growth conditions (958C), the levels of mRNA and protein appear to decrease rapidly as detected by Northern and Western blot, respectively (Laksanalamai, Lowe and Robb, unpublished results).…”
Section: Stabilization Of Taq Polymerase By a Combination Of Prefoldimentioning
confidence: 92%
“…Pyrococcus furiosus sHsp and Hsp60 were cloned, expressed, and purified as previously described by Laksanalamai et al (2001) and Emmerhoff et al (1998), respectively. The genes encoding P. furiosus Pfd a and b subunits were identified based on the homology between the P. furiosus and P. horikoshii sequences (Okochi et al, 2002).…”
Section: Preparation Of Recombinant Chaperonesmentioning
confidence: 99%
See 3 more Smart Citations